“INNOVATIVE APPROACHES IN PIANO TEACHING IN MUSIC SCHOOLS” - Akhunova , Umida (INTERNATIONAL CONFERENCES, 2023)
This article is about latest innovative approaches in piano teaching, The role of teachers in an effective piano learning.